The efficacy and safety of 225Ac-PSMA-617 in metastatic castration-resistant prostate cancer - Ma, Jiao; Zhang, Yu; Yangqing, Jiangchu; Liu, Guangfu; Wang, Junzheng; Zhang, Chunyin (Frontiers in Oncology, 2025)
BackgroundWe aimed to report our clinical experience with the use of 225Ac-PSMA-617 in the treatment of mCRPC patients.MethodsA retrospective analysis was conducted on 29 metastatic castration-resistant prostate cancer (mCRPC) patients treated with 225Ac-PSMA-617. Patients underwent treatment at 8-week intervals and discontinued treatment upon disease progression or the occurrence of intolerable adverse effects. We acquired 68Ga-PSMA-11 PET/CT images and laboratory test outcomes of patients at baseline and 8 weeks following each treatment. Short-term efficacy was evaluated through the biochemical response of serum prostate-specific antigen (PSA) and molecular tumor response criteria. A follow-up was conducted to assess the long-term effectiveness by examining the patient’s overall survival (OS) and progression-free survival (PFS). The numerical rating scale (NRS) assessed the patient’s pain. The side effects after treatment were evaluated based on common terminal criteria for adverse events version 5.0 (CTCAE v5.0).Results29 patients with mCRPC underwent a total of 50 treatment cycles. The median age of the patients was 67 years (55-84years). Out of these patients, 11 had previously underwent 177 Lu-PSMA-617 radioligand therapy (RLT). After treatment, any PSA decline was observed in 75.9% of patients, and a PSA decline≥50% was observed in 62.1%. 61.1% of patients had disease control according to molecular response. The estimated OS and PFS were 18 months (95% CI: 15-21 months) and 8 months (95% CI: 6-10 months). Univariate analysis showed that any PSA decline was positively correlated with PFS (p<0.001). The most common side effect was xerostomia, observed in 79.3% of patients. Grade III blood toxicity was observed in 7/29 patients. After treatment, the pain disappeared in 4 patients and was relieved in 13 individuals.ConclusionsIn mCRPC, the results indicated that 225Ac-PSMA-617 demonstrated a favorable disease control rate and relatively minimal side effects. However, additional high-quality randomized controlled trials are required for future validation.